Effect of altitude on essential oil composition and on glandular trichome density in three "Nepeta" species ("N. sessilifolia", "N. heliotropifolia" and "N. fissa") - Talebi, Seyed Mehdi; Nohooji, Majid Ghorbani; Yarmohammadi, Mahboobeh; Khani, Musa; Matsyura, Alex (Mediterranean Botany, 2019)
In the current study, the trichome density and the chemical variation of the hydrodistillated essential oils were determined along the altitudinal gradient in Nepeta sessilifolia, N. heliotropifolia, and N. fissa. The capitate glandular trichomes were predominant in all populations studied. Denser leaves indumentum was observed in high altitude populations of N. heliotropifolia, and in low altitude populations of N. sessilifolia and N. fissa. Moreover, the inter-population chemical polymorphism was detected. In the lower population of N. sessilifolia, spathulenol (14.2%) was the major compound of essential oils. This oil had great amount of oxygenated sesquiterpene (35.3%), while the oil of high altitude population had great amount of diterpenes, namely phytol (32.8%). In N. fissa, the main compound in lower population was β-caryophyllene (33.1%), whereas in the higher population it was caryophyllene oxide (21.5%). In N. heliotropifolia, 1,8-cineole (20.1%) was as the principal oil compound in low altitude population and β-caryophyllene (18.8%) in the high altitude population. We suggested that the amount of different types of monoterpenes decreases along the altitudinal gradient and the amount of oxygenated compounds increases with the elevation.